Entrepreneurial Elements of Activity for Value-Based Selling -A Product Centric Perspective Model - Tolymat, Ahmed Raafat; Abdelaziz, Rasha; Salam, Mohamed Abdel; Shawky, Ayman (Journal of Entrepreneurship and Project Management, 2023)
Purpose: The successful implementation of VBS entails eight process elements of activity Yet Practical application showed a difference between theory and practice when its about to turning the concept into action in entrepreneurial domain, to address this gap this study aims to contribut to the improvement of the VBS implementation processes by exploring and designing a Product Centric VBS model for entrepreneurs, and by doing this to contribute to the general body of knowledge of VBS. Methodology: The research design builds on the Descriptive practice-oriented research methodology. Findings: While our study confirms earlier research on value-based selling antecedes and consequences we also identify epistemological assumption that the marketing organizational tier is the appropriate level for initiating VBS elements of activity hence the value co-creation process will be rationally superseded by value pre-crafting in collaboration between supplier and transitional entrepreneur. Unique Contributions to Theory, Policy and Practice: As earlier studies for Successful implementation of value-based selling and the conceptualization of the approach adopted a customer value co-creation perspective. These descriptions can form first stone in the milestone for further research in which propositions could be tested based on the assumptions that we used when we elaborated the parameters that form the construct of the model that we developed.